Understanding the group process in the first year of psychotherapy: the walk, the basic assumptions and the challenges of young adults. (March 2020) - Gargiulo, Anna; Tenerini, Alessandra
This article aims to explore the dynamics of a small psychotherapy group, whose members, all young adults, began to wait for each other at the end of the sessions to walk down a stretch of road before going their separate ways. Clinical material selected from some sessions of the first year of the therapy is presented and commented on. From the possible meanings attributed to the walk, the authors highlight the group process characterized by the oscillation between the basic assumption of fight-flight and that of dependency. The work shows that the group's walk becomes, from attack to clinician, to creation of a transitional area where it is possible to experience being a young adult.